2014
DOI: 10.7888/juoeh.36.115
|View full text |Cite
|
Sign up to set email alerts
|

Lipoblast: Morphologic Features and Diagnostic Value

Abstract: Lipoblasts are conceptually a precursor or immature form of adipocytes and histologically defined as lipid-containing, mono- or multivacuolated cells possessing hyperchromatic, indented or often scalloped nuclei. They are essentially identified in neoplastic conditions and assumed to recapitulate, to some extent, the differentiation process of normal fat (adipogenesis) like their potential normal counterpart, preadipocyte or preadipose cell. Traditionally, great emphasis has been placed on the identification o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Lipoblasts are conceptually an immature or precursor form of adipocytes and are essentially identified in neoplastic conditions (12). Traditionally, great emphasis has been placed on the identification of lipoblasts as a diagnostic marker for liposarcoma (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipoblasts are conceptually an immature or precursor form of adipocytes and are essentially identified in neoplastic conditions (12). Traditionally, great emphasis has been placed on the identification of lipoblasts as a diagnostic marker for liposarcoma (10).…”
Section: Discussionmentioning
confidence: 99%
“…The nucleus of a lipoblast may be pushed aside by a single large lipid vacuole, resulting in a signet-ring configuration, or it may remain centrally located with small indentations caused by multiple, small vacuoles, resulting in an appearance similar to that of sebaceous cells or adrenal spongiocytes. In addition to the above typical lipoblast characteristics, atypical or giant forms having large, irregular or multiple nuclei may be present (12).…”
Section: Definitionsmentioning
confidence: 99%
“…Histopathological ndings in the multivariate analysis showed that lipoblasts were statistically signi cant for the diagnosis of ALT/WDLS. Traditionally, lipoblasts have been emphasized as a histopathological nding in the diagnosis of liposarcoma [36]. However, lipoblasts are also observed in benign lipogenic tumors such as spindle cell/pleomorphic lipoma.…”
Section: Discussionmentioning
confidence: 99%
“…Chung and Enzinger described infiltration into the surrounding skeletal muscle and lesser lobulation as important features differentiating lipoblastomatosis from typical lipoblastoma (8). Lipoblast is a unique mesenchymal cell that ranges in morphology from an immature fat cell resembling fibroblast to a mature fat cell with lipid droplets throughout its cytoplasm (9). There are many histomorphological mimics of lipoblasts which pose difficulty in making the correct diagnosis (Table 1) (9).…”
Section: Discussion and Review Of Literaturementioning
confidence: 99%